How do long COVID patients perceive their current life situation and occupational perspective? Results of a qualitative interview study in Germany - Schmachtenberg, Tim; Müller, Frank; Kranz, Jennifer; Dragaqina, Anita; Wegener, Greta; Königs, Gloria; Roder, Sascha (Frontiers in Public Health, 2023)
Introduction Many people experience persistent or new-onset symptoms such as fatigue or cognitive problems after an acute infection with COVID-19. This phenomenon, known as long COVID, impacts physical and mental wellbeing, and may affect perceived quality of life and occupational perspectives likewise. The aim of this study is to gain a deeper understanding of how people with long COVID experience health-related restrictions in their daily life and their occupational situation, and to identify key challenges they face. Methods Guided qualitative interviews were conducted with 25 people with long COVID. The interviews were transcribed according to Dresing/Pehl and Kuckartz and analyzed using qualitative content analysis. Afterward, a systematic comparison of the data and a reflection under consideration of lifeworld-theoretical approaches (Berger and Luckmann) were carried out. Results The interviews revealed that many participants have severe symptoms which strongly impair them in perform daily and work-related activities, and in their personal interests. Many interviewees already reach their stress limit during routine household activities or childcare. Of the 25 participants, 19 experienced limitations in pursuing leisure activities, and 10 of the 23 interviewees with jobs reported being on sick leave for several months. Several respondents who had vocational reintegration are still affected by ongoing symptoms that affect their work performance considerably. This leads to uncertainty, role conflicts, a decline in social contacts, and decreased incomes, which contribute to an impairment in their quality of life. Conclusions This study shows the huge need for specific support for people with long COVID in different areas of life. To prevent people with long COVID from finding themselves in social and economic precarity, decision-makers should develop strategies to systematically support them in their sustainable reintegration into the workforce. The focus should be on creating long COVID-sensitive workplaces, compensating for decreased incomes, and improving access to relief services such as vocational reintegration. We argue, that a shift of perspectives is necessary and that long COVID should be considered rather as a “social disease” with considerably impairments in the social life of those affected. Trial registration The study is registered in the German register for clinical trials (DRKS00026007).